2014
DOI: 10.1093/mnras/stt2317
|View full text |Cite
|
Sign up to set email alerts
|

Interacting galaxies: corotating and counter-rotating systems with tidal tails

Abstract: We analyse interacting galaxy pairs with evidence of tidal features in the Sloan Digital Sky Survey Data Release 7 (SDSS-DR7). The pairs were selected within z < 0.1 by requiring a projected separation r p < 50 h −1 kpc and relative radial velocity ∆V < 500 km s −1 . We complete spectroscopic pairs using galaxies with photometric redshifts considering ∆V phot < 6800 km s −1 , taking into account the mean photometric redshift uncertainty. We classify by visual inspection pairs of spirals into co-rotating and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
(59 reference statements)
3
21
1
Order By: Relevance
“…This tendency is stronger for galaxy pairs highlighting that the photometric data described in section 2 is useful to complete the sample of close pairs. These results are in agreement with the work of Mesa et al (2014) who identify close tidal pairs by looking for photometric companions of spectroscopic galaxies. After a visual classification, these authors found that more than 60% of spectro-photometric pairs have dis- torted morphologies with features such as tidal tails and bridges or clear signs of fusion in process.…”
Section: The Effect Of Fibre Collision On System Propertiessupporting
confidence: 92%
“…This tendency is stronger for galaxy pairs highlighting that the photometric data described in section 2 is useful to complete the sample of close pairs. These results are in agreement with the work of Mesa et al (2014) who identify close tidal pairs by looking for photometric companions of spectroscopic galaxies. After a visual classification, these authors found that more than 60% of spectro-photometric pairs have dis- torted morphologies with features such as tidal tails and bridges or clear signs of fusion in process.…”
Section: The Effect Of Fibre Collision On System Propertiessupporting
confidence: 92%
“…Based on these spectroscopic results, the projected separation of r p ∼ 20 h −1 kpc and the radial velocity difference of ΔV ∼ 96 km s −1 , we confirm that the two galaxies are an interacting pair. These values agree well with some recent statistical work on the construction of galaxy pair catalogs, see Mesa et al (2014) and reference therein. In this recent paper, the authors discuss interacting galaxy pairs with evidence of tidal features in the Sloan Digital Sky Survey data release 7 (SDSS-DR7) for z < 0.1 with r p < 50 h −1 kpc and ΔV < 500 km s −1 .…”
Section: Image Enhancementsupporting
confidence: 91%
“…We have used this method previously with excellent results (e.g. Alonso et al 2007;Lambas et al 2012;Mesa et al 2014). This technique also allows us to clean the sample of galaxies immersed in groups, undetected by the software due the galaxies only have photometric information.…”
Section: Classificationmentioning
confidence: 99%
“…Throughout the history of the Universe, galaxy-galaxy interactions play a crucial role in galaxy formation and evolution according to the hierarchical model of structure formation, by linking together star formation processes with galaxies growth (Sol Alonso et al 2006;Woods & Geller 2007;Ellison et al 2010;Lambas et al 2003Lambas et al , 2012Mesa et al 2014). On the observational side, several works (e.g.…”
Section: Introductionmentioning
confidence: 99%